"The most known German poem" and possibilities of its translation (J. W. Goethe: Ein Gleiches / Wandrers Nachtlied II) - Malý, Radek (Bohemica Olomucensia, 2012)
The paper presents "the most known German poem" Ein Gleiches / Wandrers Nachtlied II written by Johann Wolfgang Goethe in 1780 and comments the possibilities of translation of this poem into Czech language. Goethe wrote this short poem (containing eight verses only) using many very ingenious formal means that with refined point together cause the outwardly simple face of the poem - but in fact the poem is very deep, ambigous text. The paper focuses on Milan Kundera's commentary on the poem in his novel Nesmrtelnost and on the most actual Radek Malý's translation of the poem.